Nurses’ awareness on hospital acquired infection risks of the geriatric patients: A descriptive and cross-sectional study - Ibrahim S S Abumettleq; Nurhan Bayraktar (Journal of Infection in Developing Countries)
Introduction: The increasing number of persons > 65 years of age form a special population at risk for nosocomial and other health care-associated infections. Nosocomial infections are major problems in terms of morbidity and mortality as well as prolonged hospitalization and increased costs. The aim of the present study was determination of nurses’ awareness of hospital-acquired infection risks of the geriatric patients.